Transport connectivity for remote communities in Scotland - James Laird (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This report looks at the transport challenges for remote areas in Scotland. It does so by examining innovative policies the government has developed to ensure communities on both the margins of the country and the economy are connected to the rest of the country. It takes a broad view of connectivity, examining the crucial role transport plays in the provision health and education services.
Keywords: 330